Mass balances and distributions of C, N, and P in the anaerobic digestion of different substrates and relationships between products and substrates - Li, H.; Tan, F.; Ke, L.; Xia, D.; Wang, Y.; He, N.; Zheng, Y.; Zheng, Y.
Knowledge of the distributions and mass balances of C, N, and P during anaerobic digestion (AD)processes serves several purposes; for instance, these values can be used to obtain reliable quantitative information on the fate of C, N, and P after AD, to understand carbon and nutrient balances, and to evaluate the contribution of AD processes to elemental cycles. In this paper, C, N, and P contents in the gas, liquid and solid phases were investigated for seven different substrates: corn straw, rice straw, wheat straw, swine manure from pigs fed feedstuff or foodstuff, cattle manure, and chicken manure. The conversion efficiency of C in a substrate into methane was found to be highest in swine manure from pigs fed foodstuff (15.8 percent), and greater liquid and solid stream nutrient levels were found in the swine manures and chicken manure than in the cattle manure and straws. The mass balances of C, N and P for each different substrate were distinct, but all balances were close to 100 percent in this study. Further study revealed that CH4 yields and substrate lignin fitted a linear negative relationship well, and the COD/TOC, NH4 +-N and TP concentrations in the supernatant had positive linear relationships with the proteins, TAN/proteins and potassium of substrates, respectively.
Keywords: ANIMALS; CARBON; FERTILIZERS; LIQUID METHANE; MANURES; METHANE; NUTRIENTS; SUBSTRATES; CHICKEN MANURE; DIFFERENT SUBSTRATES; DISTRIBUTION; LINEAR RELATIONSHIPS; NUTRIENT BALANCE; ORGANIC WASTES; QUANTITATIVE INFORMATION; QUANTITATIVE INFORMATION